E-knowlledge aset - Zilah, Amirul Firdaus; Mat Ripin, Mohd Hamimi; Mohd Rozid, Siti Asma; Musa, Siti Marzattulaznee; Ismail, Mohd Fadzli (Universiti Teknologi MARA, Kedah, 2014)
E-knowlledge aset is a document management system in the form of electronic open source. The use of the document management system is to assist an organization to increase its productivity in managing existing information in order to become more effective. Through this system, all information generated by field experts can be referred by all. E-knowlledge aset is the first alternative designed to facilitate work in managing information. E-knowlledge aset is the first solution for information system management to store existing information and newly produced information for sharing and reference to other UMK community.